Visual Function and Brief Cognitive Assessment for Multiple Sclerosis in Optic Neuritis Clinically Isolated Syndrome Patients. Issue 1 (23rd March 2022) - Collorone, Sara; Kanber, Baris; Hashem, Leen; Cawley, Niamh; Prados, Ferran; Davagnanam, Indran; Barkhof, Frederik; Ciccarelli, Olga; Toosy, Ahmed
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: In this study, we hypothesized that clinically isolated syndrome–optic neuritis patients may have disturbances in neuropsychological functions related to visual processes. Methods: Forty-two patients with optic neuritis within 3 months from onset and 13 healthy controls were assessed at baseline and 6 months with MRI (brain volumes, lesion load, and optic radiation lesion volume) and optical coherence tomography (OCT) (peripapillary retinal nerve fiber layer [RNFL], ganglion cell and inner plexiform layers [GCIPLs], and inner nuclear layer). Patients underwent the brief cognitive assessment for multiple sclerosis, high-contrast and low-contrast letter acuity, and color vision. Results: At baseline, patients had impaired visual function, had GCIPL thinning in both eyes, and performed below the normative average in the visual-related tests: Symbol Digit Modalities Test and Brief Visuospatial Memory Test-Revised (BVMT-R). Over time, improvement in visual function in the affected eye was predicted by baseline GCIPL ( P = 0.015), RNFL decreased, and the BVMT-R improved ( P = 0.001). Improvement in BVMT-R was associated with improvement in the high-contrast letter acuity of the affected eye ( P = 0.03), independently of OCT and MRI metrics. Conclusion: Cognitive testing, assessed binocularly, of visuospatial processing is affected after unilateral optic neuritis and improves over time with visual recovery. This is not related to structural markers of the visual or central nervous system.